Cora’s Racism Analysis as Seen in Whitehead’s The Underground Railroad (2016) - Rahdeesse Bangun Mustika Dewa; Budianto, Lestari (Journal of Applied Linguistics and English Education, 2024)
Racism is unfair different treatment of people in society. The purpose of this study to describethe form of racism in Cora in The Underground Railroad. Cora’s racism at The Underground Railroad is one of social problem held in the novel. This study used qualitative approach as the method. The data of the study were Cora’s action, utterances, narration, other character action to Cora in The Underground Railroad. The writer collected the data by underlining the sentences reading the novel many times, identifying racism actions, analyzing the data, and concluded the data. Cora’s racism in The Underground Railroad showed how Cora suffered during enslaved by her master even her effort to run away from her master. The writer founds five forms of Cora’s racism were discrimination, prejudice, segregation, stereotypes, and violence. The most of racial practices and many kinds of violence had experienced by Cora for being enslaved by her master.